Integrated Analysis of Land Subsidence from Alluvium Formation Based on Conventional Deep Pipe Monitoring (CDPM) and Geotechnical Parameters in Pekalongan and Surrounding Areas, Indonesia - Dita Arif Yuwana; Dicky Muslim; T Yan WM Iskandarsyah; Saut Sagala; Wawan Hermawan; Taufiq Wirabuana; Kharis Aulia Alam; Muhammad Asa; Akhirul Insan (Geological Agency, 2026)
Despite being densely populated and economically thriving, the northern coast of Java, specifically Pekalongan, encounters significant challenges to further development, notably land subsidence. Since the late 2000s, these hazards have become increasingly evident, causing infrastructure damage and displacing residents. Alluvial deposits are formations that provide insight into unconsolidated sediment affecting land subsidence. This study integrated land subsidence in alluvial deposits at nine Conventional Deep Pipe Monitoring (CDPM) spread between 2021 and 2025, Standard Penetration Test (SPT) results, geotechnical analysis, including Compressibility Index (Cc), and Activity Ratio (Ac) of undisturbed samples to assess the mechanisms of subsidence and spatial variability. The alluvium formation observation results are separated into three groups: fluvial deposit group 1, marsh-swamp deposit group, and fluvial deposit group 2. The average SPT test was the softest, measuring 8.9 in Wonokerto and 11.1 in Kandang Panjang, for the biggest CDPM decrease of -3.89 cm/year in Wonokerto and -3.24 cm/year in Tirto annually. Wonokerto and Depok have the biggest clay sediment accumulations, measuring 43.3 m and 43 m, respectively. Then, at depths approximately 10 m to 22 m below the surface, laboratory testing revealed that the highest values for (Cc) are 0.1 to 0.7, and (Ac) are 1.3 to 1.5. The study findings show that areas with thick soft clay layers and high compressibility exhibit the highest subsidence rates, exceeding more than -2.5 cm/year in the central northern region of the studied area in Wonokerto, Tirto, and Hoegeng. The average land subsidence is positively correlated with the average SPT and the accumulation of clay sediments. According to Cc, Ac, and SPT values, the marsh-swamp deposit group has the biggest impact on land subsidence with approximately depth range of -10 m to 40 m that categorized as “Very High Potential Risk”. In the end, this study offers a more secure framework for building infrastructure in regions vulnerable to land subsidence.